2020
DOI: 10.1155/2020/2510951
|View full text |Cite
|
Sign up to set email alerts
|

PPARG Could Work as a Valid Therapeutic Strategy for the Treatment of Lung Squamous Cell Carcinoma

Abstract: Previous studies showed that PPAR-gamma (PPARG) ligands might serve as potential therapeutic agents for nonsmall cell lung cancer (NSCLC). However, a few studies reported the specific relationship between PPARG and lung squamous cell carcinoma (LSCC). Here, we made an effort to explore the relationship between PPARG and LSCC. First, we used mega-analysis and partial mega-analysis to analyze the effects of PPARG on LSCC by using 12 independent LSCC expression datasets (285 healthy controls and 375 LSCC cases). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Increasing evidence has indicated that PPAR-g agonists may serve as master modulators for overcoming classic obstacles associated with targeted NSCLC therapies, including resistance to therapy and tumor genetic heterogeneity (144)(145)(146). These examples strongly suggest that PPAR-g has potential as a molecular target for NSCLC treatment (129,(147)(148)(149).…”
Section: Pgc-1a/ppar-g Signaling In Hypoxia-induced Chemoresistance In Nsclcmentioning
confidence: 99%
“…Increasing evidence has indicated that PPAR-g agonists may serve as master modulators for overcoming classic obstacles associated with targeted NSCLC therapies, including resistance to therapy and tumor genetic heterogeneity (144)(145)(146). These examples strongly suggest that PPAR-g has potential as a molecular target for NSCLC treatment (129,(147)(148)(149).…”
Section: Pgc-1a/ppar-g Signaling In Hypoxia-induced Chemoresistance In Nsclcmentioning
confidence: 99%
“…PPARs are ligand-activated transcription factors which belong to the nuclear receptor superfamily including PPARα, PPARβ/δ, and PPARγ three isoforms [5,6]. PPARs interact with other transcription regulators to regulate the transcription of its target genes involved in energy metabolism and important cellular biological functions like inflammation, cellular proliferation, and differentiation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of NFIX expression can inhibit the proliferation, migration, and invasion of lung cancer cell lines [ 14 ]. Studies have shown that activation of peroxisome proliferator-activated receptor-gamma (PPARGγ) may inhibit the progression of lung squamous cell carcinoma (LSCC) through the regulation of upstream and downstream marker genes of LSCC, and these genes are involved in tumor-cell proliferation and protein polyubiquitination/ubiquitination [ 15 ]. Inositol 1,4,5-trisphosphate 3-kinase (ITPKA), a member of the inositol polyphosphate kinase (IPK) family, regulates the level of inositol polyphosphate, which is critical for transduction of cell signals.…”
Section: Discussionmentioning
confidence: 99%